Early labour experience questionnaire: Psychometric testing and women's experiences in a Swedish setting. (September 2018) - Ängeby, Karin; Sandin-Bojö, Ann-Kristin; Persenius, Mona; Wilde-Larsson, Bodil
Abstract: Objective: (a) to psychometrically test the Early Labour Experience Questionnaire (ELEQ) among both primi- and multiparous women giving birth in a Swedish setting, and (b) to describe and compare their experiences during early labour in relation to background characteristics. Design: a cross-sectional study. Setting: a county in Sweden. Participants: primi- and multiparous women with a spontaneous onset of labour after gestational week 37 + 0. In total, n  = 1193 women were invited, and n  = 754 responded the questionnaire, with a final total of n  = 344 primi and n  = 410 multiparous women. Methods: the ELEQ was translated with cross-cultural adaptation. The validity was determined using exploratory factor analysis with principal axis factoring analyses. Reliability was estimated from the internal consistency using Cronbach's alpha. The relationship between the questionnaire and the demographic characteristics of the participating women were analysed using ANOVA and t -test. Findings: an explorative factor analysis showed a three-factor solution for primiparas women (SWE-ELEQ-PP) consist of 23 items and a stable factor structure that explained 49.2% of the total variance with sufficient reliability coefficients (0.81–0.86). A four-factor solution for multiparous women (SWE-ELEQ-MP) consist of 22 items, with 52.62% of the total variance explained and with adequate internal consistency reliability coefficients (0.77–0.86) for three factors and relatively low stability (0.62) for the fourth factor with two items. Primiparous women scored significantly higher on items about feeling confused, and significantly lower on some items measuring emotional wellbeing and perceptions of midwifery care compared to multiparous women. Primiparous women with longer early labour (>18 h), scored significantly lower on the perceptions of midwifery care. Primi- and multiparous women who were dissatisfied with their telephone conversation or with not being admitted during early labour, scored significantly lower on emotional wellbeing, higher regarding emotional distress, and significantly lower about perceptions of midwifery care. Key conclusions: the SWE-ELEQ-PP and SWE-ELEQ-MP are considered valid questionnaires for use in a Swedish setting. Differences exist between parity and the factor structure and experiences in early labour vary. Women less content with early labour management decisions rated perceived midwifery care lower regardless of parity. Implication for practice: the questionnaire can be used to evaluate early labour care in a Swedish setting. The result suggests that differences according to parity exist and should be addressed when managing early labour care and a more individualised approach requires considerations.